Low-crosstalk silicon-photonics arrayed waveguide gratings integrated with micro-ring filter - Liu, Shiping; Hu, Heming; Ma, Xiaoyue; Dong, Runyu; Fang, Qing; Chen, Hua (Frontiers in Physics, 2022)
A low-crosstalk compact arrayed waveguide grating integrated with a tunable micro-ring resonator is demonstrated on SOI platform, The side-lobe of the silicon nanowire AWG, introduced by fabrication errors, can be effectively suppressed by the Ring Filter, The crosstalk level of the side-lobe can be reduced from -16.3dB to -26.8dB, in addition, the crosstalk of integrate AWG have improved over the entire 3dB bandwidth, with a maximum crosstalk improvement of 8.9dB at the left and right wavelengths of the 3dB bandwidth, and the excess loss from the ring resonator can be ignorable in principle.